The Health Regulatory Effect of Lactic Acid Bacteria on Human Body - Guan, Yichen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Probiotics are a kind of active microorganisms that are beneficial to the host by colonizing in the human body and changing the composition of the flora in a certain part of the host. The organic acids, special enzymes and actinomycin’s produced by lactic acid bacteria (LAB) have special physiological functions. LAB can regulate the normal flora of gastrointestinal tract and maintain the microecological balance, so as to improve gastrointestinal function, increase food digestibility and biotiter, reduce serum cholesterol, control endotoxin, inhibit the growth of spoilage bacteria in intestinal tract, and improve body immunity. This paper studied the existence mode and influencing factors of probiotics and took LAB as an example to mainly describe the research progress of LAB in probiotics, discussed the mechanism of probiotics to maintain the ecological balance of intestinal flora, summarized the impact of probiotics on human body, and aimed at various problems and deficiencies faced by the probiotic industry at present. Some suggestions on the future research direction are put forward.